Wireless and Mobile Networking - Hassan, Mahbub, author 346055 (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2022)
"The book is a textbook on wireless and mobile networking. It covers the fundamental issues in wireless networking and in mobile contexts. It explains the latest standards and research efforts on the topic. The book is also useful as a reference for computer professionals. It is meant to be for professionals and students with computer science background"--